(untitled) (Journal of the College of Basic Education, 2022)
This research deals with the phenomenon of self-poetry in the first Abbasid period, taking the poetry of Abdullah Ibn Al-Mubarak as a model.Hence, the research came distributed between a brief presentation of this phenomenon among poets in the era of the poet, and between its motives and manifestations according to Abdullah bin Al-Mubarak.Submission: